Bug bounty bootcamp : the guide to finding and reporting web vulnerabilities - Li, Vickie (No Starch Press, 2021)
"A comprehensive guide designed to prepare any application security tester for participation in bug bounty programs. Beginning with a thorough overview of how to get started in the bug bounty industry, the book then dives into how to prevent, exploit, and escalate specific vulnerabilities before concluding with in-depth techniques for the experienced hacker"--